Pelatihan Penyusunan Karya Tulis Ilmiah dalam Meningkatkan Minat dan Bakat Siswa-Siswi di SMAN 2 Mranggen - Fitria Maya Lestari; Risdiana Cholifatul Afifah; Nurti Kusuma Anggraini; Etika Herdiarti (Faculty of Engineering, Universitas Semarang, 2024)
This Community Service activity aims to strengthen the added value of each student through the ability to read and write academic and non-academic articles. Community service methods through tutorials, workshops, and assignments which are synergized with life skills teaching and extracurricular activities at SMAN 2 Mranggen. The service team, which consists of lecturers and students, works together by conducting training and supporting SMAN 2 Mranggen students in designing writing frameworks, creating writings, and publishing them in competitions, media, and newspapers. Considering the new normal situation after the COVID-19 pandemic, training can be carried out face-to-face with the PKM Team and training participants. In carrying out the training, we have coordinated together according to the time and place that has been determined. way of thinking, perspective, and behavior of SMAN 2 Mranggen students to participate individually and in groups in environmentally friendly activities to create an efficient and responsible lifestyle for the future. It can be concluded that this PKM activity has created a foundation of learning experiences and skills that enable students to describe their thoughts in a clear, sequential, logical language, taught practical ways of writing KTI, and detailed in the educational process of secondary education and then in higher education. Provides benefits if it is introduced in high school.